Peran Keluarga, Lingkungan Sekolah, dan Media Sosial dalam Pembentukan Sikap Religius Siswa di Sekolah Dasar - Nurhaibah Purba; Rizka Harfiani; Widya Masitah (Jurnal Humanitas: Katalisator Perubahan dan Inovator Pendidikan, 2025)
This study aims to analyze the role of family, school environment and social media in the formation of religious attitudes of students at SDN 102116 Gunung Pamela. The research approach used is qualitative research with a descriptive type. Data were collected through observation, interviews and documentation with the principal, teachers, students and parents. Then, it was analyzed with steps, namely data collection, data condensation, data presentation and Conclusion. The technique of testing the validity of this research data uses source triangulation and technical triangulation. The results of this study, namely accompanying their children in playing, providing guidance and direction to children, providing good examples to children and teaching children about God, His Prophet, and the teachings of the Qur'an and Hadith. The role of parents is to foster good relationships with children, as facilitators and as role models. The role of the school environment in the formation of students' religious attitudes by praying before learning, welcoming students, praying in congregation, infaq/shodaqoh, holding religious holidays such as halal bihalal, isra' miraj, maulid and deepening of religion. The role of social media in the formation of students' religious attitudes is to see educational content, display educational content and encourage students to do good. The Conclusion of this study states that family, school environment and social media have an important role in the formation of students' religious attitudes.